2012
DOI: 10.1523/jneurosci.0647-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Neurofilament Medium C Terminus Increases Axonal Diameter Independent of Increases in Conduction Velocity or Myelin Thickness

Abstract: Maturation of the peripheral nervous system requires specification of axonal diameter, which, in turn, has a significant influence on nerve conduction velocity. Radial axonal growth initiates with myelination, and is dependent upon the C-terminus region of neurofilament medium (NF-M). Molecular phylogenetic analysis in mammals suggested that expanded NF-M C-termini correlated with larger diameter axons. We utilized gene targeting and computational modeling to test this new hypothesis. Increasing the length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 39 publications
0
64
0
Order By: Relevance
“…Indeed, the induction of Boc expression in those cells was found to specifically induce a high NF-M expression (Vuong et al, 2017). The role of NF-M in the radial growth of both large (>2 µm) and small (<2 µm) classes of myelinated fibres has been thoroughly investigated mainly in the peripheral nervous system where this process is necessary for the rapid impulse transmission in axons with a diameter over 1 µm (Eyer and Peterson, 1994;Garcia et al, 2003;Barry et al, 2012;Yuan and Nixon, 2016). Therefore, although further work is required to demonstrate a potential link between the altered radial growth of the callosal axons and the decreased expression of the neurofilament NF-M, both phenotypic features are likely to impair the fine tuning of postnatal active myelination in the absence of functional Boc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the induction of Boc expression in those cells was found to specifically induce a high NF-M expression (Vuong et al, 2017). The role of NF-M in the radial growth of both large (>2 µm) and small (<2 µm) classes of myelinated fibres has been thoroughly investigated mainly in the peripheral nervous system where this process is necessary for the rapid impulse transmission in axons with a diameter over 1 µm (Eyer and Peterson, 1994;Garcia et al, 2003;Barry et al, 2012;Yuan and Nixon, 2016). Therefore, although further work is required to demonstrate a potential link between the altered radial growth of the callosal axons and the decreased expression of the neurofilament NF-M, both phenotypic features are likely to impair the fine tuning of postnatal active myelination in the absence of functional Boc.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that myelinating Schwann cells locally modulate neurofilament phosphorylation, axonal calibre and slow axonal transport . It has been suggested that this regulation is mediated by the myelin‐associated glycoprotein , but the mechanisms involved are not understood . Glutamate receptors have also been highlighted as potential determinants of neurofilament transport .…”
Section: Neurofilament Composition Transport and Regulationmentioning
confidence: 99%
“…When we analysed the data with regard to PTM distributions within proteins for closely spaced sites of modification [31] we observed that those proteins which were heavily modified overlapped very well with those which were regulated, suggesting that regulation and heavy modification target the same functional areas during brain development and may be in some way linked (note that 'heavy modification' here indicates two or more PTMs of any type investigated within five residues of one another). Of particular interest was that, in addition to the generally good overlap between regulation and heavy modification, proteins which were heavily modified included many of the same structural proteins; neurofilament heavy polypeptide (NFH), for instance, a component of neurofilaments (which form much of the neuronal cytoskeleton and have a central function in controlling developing axon diameter [64]), was very heavily modified by both phosphorylation and acetylation at a repeated KSP motif. This protein is known to be phosphorylated [42] (though not acetylated), and was here observed to contain 14 triple PTM repeats (i.e.…”
Section: Namementioning
confidence: 99%